Ventricular morphology of single-ventricle hearts has a significant impact on outcomes after Fontan palliation: a meta-analysis. (11th November 2022) - Ponzoni, Matteo; Azzolina, Danila; Vedovelli, Luca; Gregori, Dario; Di Salvo, Giovanni; D'Udekem, Yves; Vida, Vladimiro; Padalino, Massimo A
Abstract: OBJECTIVES: A conclusive interpretation of the role of ventricular dominance in outcomes after Fontan palliation has not been formulated yet. We conducted a systematic review and meta-analysis of scientific literature to give an insight into the impact of ventricular morphology in single-ventricle palliation, focusing on its influence on survival, morbidities, ventricular performance and functional capacity. METHODS: A systematic review of PubMed, Web of Science and Scopus databases was performed. A random-effect meta-analysis was conducted, and survival data were reconstructed using the published Kaplan–Meier survival curves. RESULTS: Twenty-seven studies were selected, for a total of 4529 left-dominant versus 4844 right-dominant patients. Estimated survival at 1, 5, 10, 20 and 30 years of follow-up was 0.99 [95% confidence interval (CI) = 0.98–0.99], 0.95 [95% CI = 0.94–0.96], 0.92 [95% CI = 0.91–0.93], 0.86 [95% CI = 0.84–0.88] and 0.68 [95% CI = 0.65–0.83] for left-dominant patients and 0.94 [95% CI = 0.93–0.95], 0.89 [95% CI = 0.88–0.9], 0.85 [95% CI = 0.83–0.87], 0.69 [95% CI = 0.63–0.75] and 0.59 [95% CI = 0.5–0.69] for right-dominant patients, respectively. Survival was statistically lower for right-dominant patients ( P  < 0.001), with an hazard ratio for the mortality of 2.38 (2.03–2.80); also, they displayed significantly longer hospital stay, worse ventricular function, larger ventricular volumes and a higher incidence of moderate or severe atrioventricular valve regurgitation when compared to left-dominant patients. CONCLUSIONS: According to our meta-analysis, the morphology of the dominant ventricle has a significant impact on outcomes after Fontan palliation. Right-dominant patients experience an inferior long-term survival when the anatomical right ventricle is included in the systemic circulation. Abstract : Five decades after the first surgical treatment for a single-ventricle (SV) cardiac anomaly by Fontan and Baudet [1], the most recent series are reporting excellent long-term survival after Fontan operation [2].